Synergy hub designing a multifunctional e-commerce complex for enhanced regulatory and logistical support - Quirante, Carmella Anne; Ruby Teresa M. de Leon (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
This research focused on developing an architectural solution to support the regulatory and
consumer protection needs of the Philippine e-commerce sector. With the rapid growth of
online transactions, the need for a centralized facility that integrates regulatory oversight,
business support, and consumer advocacy became evident. The study aimed to design an
e-commerce center that met the operational needs of the Department of Trade and Industry
(DTI) E-commerce Bureau while providing spaces for business development and consumer
assistance. The research sought to explore how architectural design could address the
operational requirements of the DTI E-commerce Bureau, promote synergy between
regulatory, business, and consumer functions, and ensure inclusivity, accessibility, and
adaptability within a dynamic e-commerce environment. To achieve these goals, a
mixed-methods approach was employed, which involved analyzing data from government
publications, official reports, and relevant academic studies. These methods informed the
design process by offering insights into the needs of various stakeholders and the workflows
required to support effective regulation and consumer protection. This holds significance in
addressing the challenges of e-commerce governance in the Philippines. This project
proposed a functional and adaptable architectural framework to enhance the DTI
E-commerce Bureau's ability to regulate the industry, support businesses, and protect
consumers. Furthermore, it sought to demonstrate how architecture can respond to emerging
societal and technological needs, potentially serving as a reference for similar initiatives in
the future.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Electronic commerce -- Buildings; Consumer protection -- Philippines; Electronic commerce -- Philippines